If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 70 = 11 + -3x Solving 70 = 11 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 70 + 3x = 11 + -3x + 3x Combine like terms: -3x + 3x = 0 70 + 3x = 11 + 0 70 + 3x = 11 Add '-70' to each side of the equation. 70 + -70 + 3x = 11 + -70 Combine like terms: 70 + -70 = 0 0 + 3x = 11 + -70 3x = 11 + -70 Combine like terms: 11 + -70 = -59 3x = -59 Divide each side by '3'. x = -19.66666667 Simplifying x = -19.66666667
| 4p-7(p+8)= | | -51+12x=-123 | | 11-3x=70 | | 8(t^2-2t+5)+4(t^2-3t+2)-6(2t^2-8)= | | -16+9x=56 | | -3(7p+5)-2(2-20p)=3(7+6p) | | 4x-5=-2 | | 5n+5-3n+2+4n= | | -11x-92=73 | | 2v^2+4v-16=0 | | (x^2+8x+7)-(x^2-2x+1)=36 | | 117.15-105=0.15m | | x^2+16x+48=0 | | -5x-21=-61 | | 3u^2=18u-9 | | 3m-7.6=26.9 | | C^9-1=-10 | | .3(20r+6)-(r-3)= | | 5-9(3x-4)=7(x+2) | | (2x-4)(x-3)=0 | | -3x+10=-17 | | 2x+8=14-x | | 5h+3=18.5 | | 2(5r+4)-4(r-3)-16r= | | -6+-1= | | 7(p+1)=-p | | 5y-2= | | 5.7x-2x=14.8 | | 11x+7-4=10x-2 | | 3(5-c)-33=21c-6(3+4c) | | 5x+x=9+4x-1+6 | | -6+2r-3= |